The role of legal due diligence in ensuring legal certainty in business transactions in Indonesia - Radea Respati Paramudhita (Cessie : Jurnal Ilmiah Hukum, 2025)
This study aims to analyze the role of Legal Due Diligence (LDD) in ensuring legal certainty in business transactions in Indonesia. In the context of an increasingly complex business world, LDD serves as a preventive instrument to identify and mitigate legal risks that may arise before a transaction is executed. This study uses a qualitative method with a normative juridical approach, through a literature review and analysis of laws and regulations, legal doctrine, and legal practices in Indonesia. The results indicate that the implementation of Legal Due Diligence (LDD) plays a crucial role in ensuring legal certainty and increasing trust in every business transaction in Indonesia. Through a thorough examination of legal aspects, such as asset ownership, regulatory compliance, financial condition, and potential disputes, LDD is able to identify various legal risks that may arise before a transaction is executed. The findings also indicate that companies that consistently implement LDD tend to be better protected from legal issues and have a stronger bargaining position in business negotiations.